The Relationship Between Assignment Methods and Social Interaction With The Level Of Student Learning Activeness at Madrasah Ibtidaiyah Darul Ulum Tandes - Dia Rahmawati; Didit Darmawan (International Journal of Islamic Thought and Humanities, 2024)
Education is crucial in shaping and optimizing students' potential to succeed. One sign of educational success is the level of student participation in learning activities, which reflects the level of student involvement and activity in the learning process. This research analyses the influence of assignment methods and social interaction on students' active learning at Islamic Elementary School or Madrasah Ibtidaiyah (MI) Darul Ulum Tandes. This research involved 216 MI Darul Ulum Tandes students as a population, with 36 class VI students selected as samples using total sampling. The research results show that the assignment method significantly influences students' active learning. This method provides opportunities for students to apply the concepts learned and encourages their direct involvement in the learning process. Social interactions also have a significant impact, engaging students in communication, collaboration, and emotional connection. This research makes a theoretical contribution by improving understanding the complexity of the relationship between learning methods and social interaction.